MONOAMINE OXIDASE-A ENZYME ON KINTAMANI DOGS IN BALI, INDONESIA - Siswanto,; dharmawan, Nyoman Sadra; Puja, I Ketut; Putra, I Gusti Agung Arta (Buletin Veteriner Udayana, 2025)
The enzyme monoamine oxidase-A (MAO-A) is a compound that can break down serotonin. So if the level of monoamine oxidase-A in the blood is high, the level of serotonin in the blood will be low. It is known that the enzyme monoamine oxidase-A affects dog aggression. How exactly is the picture of monoamine oxidase-A in the blood of pet dogs has not been widely revealed. The purpose of this study was to determine the levels of monoamine oxidase-A in Kintamani pet dogs. Kintamani dogs are a native Indonesian dog breed found in Kintamani Village, Bali Province, Indonesia. The study used forty dogs, 15 male dogs and 15 female dogs and 10 lactating dogs. The method used in this study was the observation and cross-sectional sampling method and monoamine oxidase-A levels were determined using the elisa technique. The results showed that the average levels of monoamine oxidase-A in male Kintamani dogs (ng/ml) were 3.54 ± 1.9, females 4.85 ± 1.7 and lactating dogs 3.15 ± 2.23. The conclusion that monoamine oxidase-A level depending sex and lactating. The levels of monoamine oxidase in male dogs are lower than in female and lactating dogs. It is recommended to conduct research on the levels of monoamine oxidase A in Kintamani dogs that behave aggressively.